Complications Following Self-Administration of Hyaluronic Acid Fillers: Literature Review - Rauso, Raffaele (Clin Cosmet Investig Dermatol, 2020)
The purpose of the present study is to review published literature regarding complications following self-administration of hyaluronic acid (HA) filler. The following keywords were searched in Pubmed and Cochrane database: filler AND self injection, hyaluronic acid AND self injection; filler AND self administration; hyaluronic acid AND self administration. Two authors performed title and abstract eligibility assessment independently. Gray literature and all articles cited in the included papers were also screened and their reference lists were examined to identify other potentially pertinent studies. Non-English papers were excluded. A total of 4 complications following self injection of HA were identified. Conversely, after performing a general search through the Google Internet search engine, with the item “self-injection of hyaluronic acid filler”, there were 604,000 hits. The number of articles reporting complications after the self administration of HA is few. Despite that internet searches on the same topic shows that self-administration of HA fillers is a widely discussed phenomenon in several on-line forums. The present review suggests that complications after self-injection of HA are an under-reported phenomenon.